2007
DOI: 10.1016/j.neuint.2007.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Childhood and adolescent depression: Why do children and adults respond differently to antidepressant drugs?

Abstract: Childhood and adolescent depression is an increasingly problematic diagnosis for young people due to a lack of effective treatments for this age group. The symptoms of adult depression can be treated effectively with multiple classes of antidepressant drugs which have been developed over the years using animal and human studies. But many of the antidepressants used to treat adult depression cannot be used for pediatric depression because of a lack of efficacy and/or side effects. The reason that children and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
80
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 36 publications
3
80
0
Order By: Relevance
“…The effect seems to be greater in patients with comorbid OCD and tic disorder [61]. However, no RCT exists in pediatric OCD, and inferring that children and adolescents should benefit in the same way as adults are fraught with difficulties and depend on the presupposition that adult and pediatric OCD are equivalent, even though the transmitter systems in young people are not mature as those in adults [62]. However, naturalistic open trials using risperidone and aripiprazole as an augmentation to an SSRI in pediatric OCD indicate that the combination may be beneficial [44,63,64].…”
Section: Atypical Antipsychotics (Neuroleptics)mentioning
confidence: 99%
“…The effect seems to be greater in patients with comorbid OCD and tic disorder [61]. However, no RCT exists in pediatric OCD, and inferring that children and adolescents should benefit in the same way as adults are fraught with difficulties and depend on the presupposition that adult and pediatric OCD are equivalent, even though the transmitter systems in young people are not mature as those in adults [62]. However, naturalistic open trials using risperidone and aripiprazole as an augmentation to an SSRI in pediatric OCD indicate that the combination may be beneficial [44,63,64].…”
Section: Atypical Antipsychotics (Neuroleptics)mentioning
confidence: 99%
“…This problem is compounded in juveniles and adolescents, because there are fewer pharmacological treatment options for these patients compared with adults (Bylund and Reed, 2007). The U.S. Food and Drug Administration approved two antidepressant drugs, fluoxetine and escitalopram, for use in treating pediatric depression.…”
Section: Introductionmentioning
confidence: 99%
“…The ensuing increase in extracellular norepinephrine (NE) and 5-HT is thought to trigger therapeutic downstream events (Frazer, 1997). It has been suggested that a developmental delay in the noradrenergic central nervous system may limit the antidepressant potential of NET-targeting TCAs in juveniles and adolescents compared with adults (Bylund and Reed, 2007). However, other reports go against this idea.…”
Section: Introductionmentioning
confidence: 99%
“…Adverse events primarily include altered growth velocity, rash, dystonia, tics, affect lability, activation, metabolic blood test abnormalities, sedation, sialorrhea, and electrocardiogram irregularities [3]. Variations in terms of treatment response may be ascribed to the incomplete development of the central nervous system [4]. In particular, a major role has been attributed to the immature adrenergic system in characterizing response to psychotropic drugs in children and young adolescents [4].…”
Section: Introductionmentioning
confidence: 99%
“…Variations in terms of treatment response may be ascribed to the incomplete development of the central nervous system [4]. In particular, a major role has been attributed to the immature adrenergic system in characterizing response to psychotropic drugs in children and young adolescents [4]. Unfortunately, there is little consensus as to the assessment of adverse events in children and adolescents.…”
Section: Introductionmentioning
confidence: 99%